Divisi-Divisi Negrito Di Asia-Pasifik - Peyon, Ibrahim (Universitas Cenderawasih, 2022)
This article discusses the distribution of the Negritos in Asia and the Pacific, the Negritos are widely distributed from the Andama Islands to the Moluccas in the east, and the Philippine Islands in the north. Traces of the Negritos were also found in several areas such as Japan, Taiwan, and mainland China which are no longer found. The Negrito are the original inhabitants of the Asia and Pacific region, they live in this region as a native. The Negritos themselves admit that they are out of the land, where they live. On the other hand, paleoanthropologists, archaeologists and anthropologists say the Negritos reached the areas they lived in between 35,000 - 40,000 years ago, before the Malays invaded these areas. The population of the Negritos has been largely extinct due to foreign invasions, assimilation, and attacks by various deadly diseases. Their remains are currently found in Andama, the Malay Peninsula, southern Thailand, the islands of Timor, Molucca, and the northern Philippines. This research was carried out using descriptive methods and literature research methods from various references written by anthropologists, archaeologists, linguists, experts’ geologists and biologists. In addition, observation techniques and internet media as supporting methods in this study. The purpose of this research is to find information and data to find traces of the Negritos people, their authenticity and distribution, the remaining pockets of the Negritos and the extinction of their own ancestral land.